Stepping into the translator trainees’ shoes: a descriptive study - Gregorio-Cano, Ana (Onomázein, 2020)
In the growing field of translation pedagogy little has been discussed about the importance of key central concepts such as translation problems, translation strategies or translator competence through empirical studies. This article examines the theoretical background as the starting point of the empirical study performed at five different universities in Spain: Universitat Jaume I (UJI), Universidad de Salamanca (USAL), Universidad Pablo de Olavide (UPO), Universidad Pontificia de Comillas (UPCO) and University of Granada (UGR). The research presented here focuses specifically on the development of translator competence and, particularly, the students’ capacity to identify translation problems. The study results demonstrate no regular patterns for the development of translator competence within the undergraduate translators and interpreters training programs in Spain.